Evaluation of Groundwater Resources in Aiyar Basin: A GIS Approach for Agricultural Planning and Development - K Balasubramani; M Gomathi; K Kumaraswamy (Geosfera Indonesia, 2019)
Groundwater is an integral part of agriculture and rural development. In the present study, an attempt has been made to analyse the spatio-temporal variations of groundwater level in Aiyar basin using spatial statistics and GIS so as to associate the variations with cropping pattern; to suggest agricultural planning and development practices. The groundwater level was measured in the basin through 40 dug wells in the months of July (pre-monsoon) and January (post-monsoon) besides water level data collected from 50 permanent monitoring wells for a period of thirty-six years (1980-2015) from the State Groundwater Division for spatial and statistical analyses. In order to understand the fluctuations in the groundwater level of the basin, seasonal groundwater levels were computed for pre and post-monsoon seasons. To understand the regional variations in water level fluctuations, hot spot analysis is carried out using Getis-Ord Gi* statistics in GIS. Based on z-score, the basin is divided into five clusters. The long-term fluctuation of groundwater level in each cluster was examined independently and the trends were determined. Based on the trend of groundwater level and cropping pattern of the clusters, suggestions are drawn for each cluster for agricultural planning and development. By comparing the clusters, it is found that the foot of Kollimalai and Pachamalai hills (cluster-4 and 5) experiences a severe drop in groundwater level. During the last 36 years, the water table of these clusters is decreased from 4 m to 10 m BGL and the rate of decline is very severe after the drought years of 2002-2003. The main reason for the declining water level in this region is the cultivation of wet crops especially paddy and sugarcane in extensive areas, although irrigation facilities are limited and the climate is conducive only for rainfed agriculture. Hence, it is necessitated to reduce the acreage of wet crops and compensate by suitable dry crops in these clusters. Keywords: Groundwater, Agriculture, GIS, Hot Spot Analysis, River basin, SDG